2022
DOI: 10.5812/ijpbs.111449
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Self-esteem and Self-efficacy in the Relationship of Perfectionism and Negative Reactivity with Eating Disorders

Abstract: Background: Eating disorders (EDs) are prevalent in adolescents and young adults, leading to various psychiatric and physical complications that affect the quality of life and even mortality. Objectives: The present study aimed to investigate the mediating role of self-efficacy and self-esteem in the relationship of perfectionism and negative reactivity with EDs. Methods: This descriptive study was performed on 302 students selected from the University of Tehran during 2018 - 2019. The data collection tools we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
4
0
2
Order By: Relevance
“…Mükemmeliyetçiliğin, YB'nin gelişmesine veya sürdürmesine yatkınlık oluşturan bir kişilik özelliği olduğu söylenmektedir (5,26,(29)(30)(31)(32).…”
Section: Sonuçunclassified
See 1 more Smart Citation
“…Mükemmeliyetçiliğin, YB'nin gelişmesine veya sürdürmesine yatkınlık oluşturan bir kişilik özelliği olduğu söylenmektedir (5,26,(29)(30)(31)(32).…”
Section: Sonuçunclassified
“…Yeme davranışında ve vücut ağırlığında ciddi sorunlarla YB karakterizedir. Ayrıca, fiziksel sağlık ve psikososyal işlevlerin önemli ölçüde bozulmasına neden olan sürekli yeme davranışları ile ilişkilidir (30). Sağlıklı kontrollere göre, YB'si olan bireyler daha yüksek düzeyde mükemmeliyetçilik göstermiştir (26).…”
Section: Sonuçunclassified
“…The present ndings indicate that among the dimensions of perfectionism, SPP was related especially strongly to both psychiatric disorders and contact with CAMHS. Theoretically, the association between perfectionism and SPP and mental distress is often explained by the self-discrepancy theory formulated by Higgins (1987), proposing that a con ict can arise between social expectations de ning an 'ideal self' in contrast with the 'actual self' among adolescents (Johnston et al, 2018) and students (Asl et al, 2022). Yet, the effect size was small for the comparison between the levels on SPP in the clinical group and reference group, and this could be explained by ndings of relatively high perfectionism scores in general youth populations (Curran & Hill, 2019; Sironic & Reeve, 2015).…”
Section: Mainmentioning
confidence: 99%
“…Perfectionism has also been described as a predisposing factor for depressive symptoms in youth (Hewitt et al, 2022), and a reciprocal relationship between maladaptive perfectionism and depressive symptoms has been reported in both clinical and non-clinical samples (Smith et al, 2021). Elevated perfectionism is also described as one of the predisposing and maintaining factors of eating disorders (Fairburn et al, 2003) and is shown to be associated with eating-related symptoms among children and adolescents in clinical samples (Johnston et al, 2018) and among students from the general population (Asl et al, 2022). According to a meta-study, this association is especially strong for self-critical perfectionistic concerns, although some studies also found this for perfectionistic strivings in early and middle adolescence (Vacca et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Male dissatisfaction with appearance, in contrast to female trends, is a complex phenomenon that includes both extremes of weight (Edwards, Tod, & Molnar, 2014). Mood disorders, distress, low self-esteem, and negative self-perceptions of attractiveness have all been linked to body image issues, as have increased social anxiety, emotional reactivity, and a propensity for pointless corrective procedures (Hayaki et al, 2002;Jung & Lee, 2006;Mousavi Asl et al, 2022).…”
Section: Introductionmentioning
confidence: 99%